Genetic variants in the IL12B gene are associated with inflammatory bowel diseases in the Korean population. Issue 10 (23rd September 2013) - Moon, Chang Mo; Shin, Dong‐Jik; Son, Nak‐Hoon; Shin, Eun‐Soon; Hong, Sung Pil; Kim, Tae Il; Kim, Won Ho; Cheon, Jae Hee
Abstract Background and Aim Recent genomic studies have identified genetic variants in the IL12B gene, which encodes the p40 subunit shared by interleukin 12 and interleukin 23, as susceptibility loci for inflammatory bowel disease (IBD). The study aimed to identify additional novel genetic variants in IL12B and investigated whether variants confer susceptibility to the development of Crohn's disease (CD) or ulcerative colitis (UC) in the Korean population. Methods To detect single nucleotide polymorphisms (SNPs) in IL12B, direct sequencing of all coding exons, exon‐intron boundaries, promoter region, and 5′ untranslated region was performed in 24 randomly selected samples. Selected haplotype‐tagging SNPs were subsequently genotyped in 493 IBD patients (245 patients with CD and 248 with UC) and 504 healthy controls. Results Two haplotype‐tagging SNPs (rs2288831 and rs919766) were selected through direct sequencing and were genotyped. Of them, SNP rs2288831 in the IL12B gene was significantly associated with CD susceptibility in allelic association analysis (odds ratio = 1.30; 95% confidence interval 1.04–1.62; P = 0.019). This significant association with CD was also observed for a haplotype consisting of SNP rs919766 and rs2288831 (odds ratio = 1.29; 95% confidence interval 1.03–1.60; P = 0.025). However, none of IL12B SNPs were associated with UC susceptibility. Finally, no specific associations between genetic variants and disease phenotype of CD were identified. Conclusions This study is first to identify SNP rs2288831 in the IL12B gene as a susceptible variation for CD. Further studies in other ethnic groups are warranted to validate the association of this genetic variant with IBD.